Melatonin Mitigates Kainic Acid-Induced Neuronal Tau Hyperphosphorylation and Memory Deficits through Alleviating ER Stress - Shi, Cai; Zeng, Jia; Li, Zixi; Chen, Qingjie; Hang, Weijian; Xia, Liangtao; Wu, Yue; Chen, Juan; Shi, Anbing (Frontiers in Molecular Neuroscience, 2018)
Kainic acid (KA) exposure causes neuronal degeneration featured by Alzheimer-like tau hyperphosphorylation and memory deficits. Melatonin (Mel) is known to protect hippocampal neurons against KA-induced damage. However, the underlying mechanisms remain elusive. In the current study, we investigated the protective effect of melatonin on KA-induced tau hyperphosphorylation by focusing on endoplasmic reticulum (ER) stress-mediated signaling pathways. By using primary hippocampal neurons and mouse brain, we showed that KA treatment specifically induced ER stress and activated GSK-3β and CDK5, two major kinases responsible for tau phosphorylation. Inhibition of ER stress efficiently inactivated GSK-3β and CDK5. Mechanistically, we found that KA-induced ER stress significantly activated calpain, a calcium-dependent protease. Inhibition of ER stress or calpain leads to the reduction in KA-induced GSK-3β and CDK5 activities and tau phosphorylation. Moreover, GSK-3β or CDK5 inhibition failed to downregulate ER stress efficiently, suggesting that ER stress functions upstream of GSK-3β or CDK5. Notably, our results revealed that melatonin acts against KA-induced neuronal degeneration and tau hyperphosphorylation via easing ER stress, further highlighting the protective role of melatonin in the KA-induced neuronal defects.